Post-Acute COVID-19 Syndrome and Stroke: Post-Acute COVID-19 Syndrome and Stroke - Araujo-Filho, Irami; Menseses Rêgo, Amália Cinthia (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2024)
This review explores the multifaceted strategies to mitigate the risk of cerebrovascular impairment in young adults recovering from COVID-19. The pandemic has illuminated an increased incidence of stroke in populations traditionally considered at lower risk, underscoring the need for targeted preventative measures. Given the complex interplay between SARS-CoV-2 infection and stroke risk, this article synthesizes current evidence and recommendations across lifestyle modifications, medical interventions, and proactive health monitoring. Key recommendations include adopting a heart-healthy diet, engaging in regular physical activity, and implementing stress reduction techniques. The management of existing cardiovascular risk factors, such as hypertension and diabetes, is emphasized as crucial for minimizing stroke risk post-COVID. Moreover, education on recognizing stroke symptoms is vital for ensuring timely medical response. The review also discusses the importance of avoiding smoking, limiting alcohol intake, and, for specific high-risk individuals, the judicious use of anticoagulants. Regular medical follow-ups for monitoring post-COVID symptoms and addressing any ongoing complications are advocated to identify and manage potential risks early. In conclusion, a comprehensive approach involving lifestyle changes, vigilant management of pre-existing conditions, education on stroke symptoms, and regular healthcare engagement is essential for reducing the risk of cerebrovascular events in young adults recovering from COVID-19. This review underscores the importance of continued research and public health advocacy in addressing the long-term effects of the pandemic on cerebrovascular health.